2005
DOI: 10.5271/sjweh.923
|View full text |Cite
|
Sign up to set email alerts
|

A new bricklayers’ method for use in the construction industry

Abstract: Objectives The aim of this study was to investigate the effect of raised bricklaying on physical workload, reported musculoskeletal disorders, sickness absence, and job satisfaction.Methods A controlled intervention study with a follow-up period of 10 months was performed among 202 bricklayers from 25 construction companies. ResultsThe introduction of devices for raised bricklaying decreased the physical load on the lower back and, to a less extent, on the shoulders and upper extremities. Although raised brick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…Therefore, an intervention aimed at reducing the weight of blocks within the range of 11 to 16 kg would not seem to be effective in reducing the risk of musculoskeletal complaints among block masons. Thus, investing in mechanical lifting equipment (Marras et al 2000) or devices to adjust working height (Marras et al 2000, Van Der Molen et al 2004a, Luijsterburg et al 2005 seems to be more appropriate as a preventive ergonomic measure. It is, however, possible that a study that used a greater range of block weights could reveal still lower block weights to be advantageous in reducing the risk of musculoskeletal complaints.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an intervention aimed at reducing the weight of blocks within the range of 11 to 16 kg would not seem to be effective in reducing the risk of musculoskeletal complaints among block masons. Thus, investing in mechanical lifting equipment (Marras et al 2000) or devices to adjust working height (Marras et al 2000, Van Der Molen et al 2004a, Luijsterburg et al 2005 seems to be more appropriate as a preventive ergonomic measure. It is, however, possible that a study that used a greater range of block weights could reveal still lower block weights to be advantageous in reducing the risk of musculoskeletal complaints.…”
Section: Implications For Practicementioning
confidence: 99%
“…Lifting devices designed for the workplaces of masons are recommended to reduce physical workload and low back complaints in the longer term , Vink et al 2002, Van Der Molen et al 2004a, Luijsterburg et al 2005. The physical nature of masonry work (Anton et al 2005) or barriers to behavioural change , however, hinder implementation and use of such engineering controls.…”
Section: Introductionmentioning
confidence: 99%
“…It can be speculated that the implemented solutions led to work that reduced light loads, repetitive work or made the work processes more efficient in general and thus less physically fatiguing. A review has shown reductions in physical work demands and musculoskeletal symptoms if mechanical lifting devices are introduced at workplaces [41], and other studies have shown a decreased discomfort [42] or ergonomic improvement when introducing devices for raised bricklaying that may decrease the physical workload during construction work [43]. Because the majority of the implemented suggestions concerned technical assistive devices, it can be speculated that the increased use of assistive devices may partially explain the decrease in general fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…These factors were considered important for the labor force participation of construction workers (12) and have also been raised by previous researchers (9,39). Until now, most health promotion programs in the construction industry have focused on improving the physical health of construction workers through a lifestyle program (40)(41)(42) or by decreasing the physical work demands by means of ergonomic measures (43).…”
Section: Discussionmentioning
confidence: 99%